A novel direct torque and flux control of permanent magnet synchronous motor with analytically-tuned PI controllers - Kenneth Odo; Chibuike Ohanu; Ifeanyi Chinaeke-Ogbuka; Augustine Ajibo; Cosmas Ogbuka; Emenike Ejiogu (Institute of Advanced Engineering and Science, 2021)
This work presents a novel direct torque and flux control (DTFC) of permanent magnet synchronous motor (PMSM) with analytically-tuned proportional integral (PI) controllers. The proportional (K_p) and integral (K_i) gains of the PI controllers were accurately determined, from first principle, using the model of the control system. The PI flux and torque controllers were then developed in rotor reference frame. The designed PI controllers, together with the torque and flux controllers, were tested on a permanent magnet synchronous motor (PMSM). The results obtained were compared with results from conventional DTFC system using manually-tuned PI controllers. The total harmonic distortion (THD) of motor phase currents is 18.80% and 4.81% for the conventional and proposed models respectively. This confirms a significant reduction in torque ripples. The control system was tested for step torque loading and found to offer excellent performance both during load changes, speed reversal, and constant load conditions.